2023
DOI: 10.7759/cureus.45840
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Information on the Treatment of Dental Hypomineralization

Hattan Zaki,
Ismail Abdouh,
Amnah Algarni
et al.

Abstract: Purpose: To categorise and evaluate the quality and readability of the web-based information about the treatment of the variety of forms of dental hypomineralization. Methods: An internet search using two different search terms regarding treating dental hypomineralization was conducted using the Google search engine. The first 100 websites from each search were analysed. Data recorded included DISCERN instrument scores, the Journal of the American Medical Association (JAMA) benchmarks, and the Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 18 publications
2
8
1
Order By: Relevance
“…In the Arabic content, of this study, none of the websites had the HON seal compared to six websites in Alpaydın et al's study [29]. The HON code seal on a medical website indicates understandable, accessible, and reliable information but does not guarantee the accuracy of the presented content [22].…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…In the Arabic content, of this study, none of the websites had the HON seal compared to six websites in Alpaydın et al's study [29]. The HON code seal on a medical website indicates understandable, accessible, and reliable information but does not guarantee the accuracy of the presented content [22].…”
Section: Discussionmentioning
confidence: 58%
“…In the era of the Internet, it is not surprising that patients use online sources to knowledge themselves about their conditions and treatment options. In the field of orthodontic treatments, multiple studies were conducted to evaluate the quality of patientcentered online content in terms of YouTube videos [27], social media tweets [28], and different website contents [29]. The aim of this study is to evaluate the quality and readability of Arabic online patientcentered information about orthodontic clear aligners in the most commonly used search engines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the tools used, the included websites were considered readable. Previous studies evaluating the readability of dental health information on various topics revealed that most of the included websites were difficult to read, targeting healthcare professionals and urging the need for simple information that the majority of patients can understand [ 16 , 23 , 25 , 26 ]. In a study evaluating the readability of online information about apicectomy in the English language, they reported a high level of difficulty [ 16 ].…”
Section: Discussionmentioning
confidence: 99%